Synthesis of Pore‐Wall‐Modified Stable COF/TiO2 Heterostructures via Site‐Specific Nucleation for an Enhanced Photoreduction of Carbon Dioxide - Akkammagari Putta Rangappa; Dharani Praveen Kumar; Khai H. Do; Jinming Wang; Yuexing Zhang; Tae Kyu Kim (Advanced Science, 2023)
Abstract Constructing stable heterostructures with appropriate active site architectures in covalent organic frameworks (COFs) can improve the active site accessibility and facilitate charge transfer, thereby increasing the catalytic efficiency. Herein, a pore‐wall modification strategy is proposed to achieve regularly arranged TiO2 nanodots (≈1.82 nm) in the pores of COFs via site‐specific nucleation. The site‐specific nucleation strategy stabilizes the TiO2 nanodots as well as enables the controlled growth of TiO2 throughout the COFs’ matrix. In a typical process, the pore wall is modified and site‐specific nucleation is induced between the metal precursors and the organic walls of the COFs through a careful ligand selection, and the strongly bonded metal precursors drive the confined growth of ultrasmall TiO2 nanodots during the subsequent hydrolysis. This will result in remarkably improved surface reactions, owing to the superior catalytic activity of TiO2 nanodots functionalized to COFs through strong NTiO bonds. Furthermore, density functional theory studies reveal that pore‐wall modification is beneficial for inducing strong interactions between the COF and TiO2 and results in a large energy transfer via the NTiO bonds. This work highlights the feasibility of developing stable COF and metal oxide based heterostructures via organic wall modifications to produce carbon fuels by artificial photosynthesis.